2015
DOI: 10.5505/turkhijyen.2015.47113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sericin protein recovered from silk wastewaters

Abstract: Objective: This study aims to determine the characteristics of sericin protein recovered from silk wastewaters. Method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…The maximal absorption wavelength indicates the absorption peaks of peptides and amino acids in sericin. 19 The amounts of amino acids differed in each type of extracted sericin, but serine was the most abundant in all samples. Serine has a high content of the hydroxyl group, which contributes to the functions of sericin.…”
Section: Discussionmentioning
confidence: 89%
“…The maximal absorption wavelength indicates the absorption peaks of peptides and amino acids in sericin. 19 The amounts of amino acids differed in each type of extracted sericin, but serine was the most abundant in all samples. Serine has a high content of the hydroxyl group, which contributes to the functions of sericin.…”
Section: Discussionmentioning
confidence: 89%
“…After that, the UV-vis absorption of sericin showed that the maximal absorption wavelength was at around 280 nm. The maximal absorption wavelength indicates the absorption peaks of peptides and amino acids in sericin (18). The amounts of amino acids differed in each type of extracted sericin, but serine was the most abundant in all samples.…”
Section: Discussionmentioning
confidence: 99%
“…All the results indicate that treatment for a period of 120min appears to be sufficient for degumming. Sericin is rich in Serine and the inner layer fibroin has high content of Alanine and glycine [13,25]. The hydrolysate obtained from skein was therefore, subjected to chromatographic run with these amino acid standards.…”
Section: Mcdamsid000585 4(2)2019mentioning
confidence: 99%
“…Molecular weight of the sericin recovered from silk wastewaters ranges from 40-176kDa [13]. Apart from its luster, the fibroin layer is known for its elasticity and tensile strength.…”
Section: Introductionmentioning
confidence: 99%